2011
DOI: 10.4317/medoral.16.e79
|View full text |Cite
|
Sign up to set email alerts
|

A novel trephine design for sinus lift lateral approach. Case report

Abstract: Various techniques are described in the literature, either by crestal or lateral approach. Sinus augmentation has a high percentage of success, but presents a number of intraoperative and postoperative complications. The most frequent complication is the Schneiderian membrane perforation with a percentage of perforations between 11% and 56% according to authors. The aim of this study is to describe another membrane approach technique for the sinus lateral wall osteotomy that minimizes the risk of Schneiderian … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 10 publications
0
4
0
2
Order By: Relevance
“…Depending on the amount and quality of residual bone, elevation of the maxillary sinus floor (the sinus lift) must be performed as a one-stage surgical procedure during implantation, with access through the alveolar ridge and a preliminarily prepared implant bed or with a lateral approach (the open method). However, there are some general disadvantages of performing the sinus floor elevation, including the maxillary sinus being lined inside with the periosteum covered with respiratory epithelium (the Schneiderian membrane) [ 7 ]. The most frequent complication after the sinus lift is the perforation of that membrane [ 7 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Depending on the amount and quality of residual bone, elevation of the maxillary sinus floor (the sinus lift) must be performed as a one-stage surgical procedure during implantation, with access through the alveolar ridge and a preliminarily prepared implant bed or with a lateral approach (the open method). However, there are some general disadvantages of performing the sinus floor elevation, including the maxillary sinus being lined inside with the periosteum covered with respiratory epithelium (the Schneiderian membrane) [ 7 ]. The most frequent complication after the sinus lift is the perforation of that membrane [ 7 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, there are some general disadvantages of performing the sinus floor elevation, including the maxillary sinus being lined inside with the periosteum covered with respiratory epithelium (the Schneiderian membrane) [ 7 ]. The most frequent complication after the sinus lift is the perforation of that membrane [ 7 10 ]. Cho et al [ 11 ] reported the rate of iatrogenic perforation of the Schneiderian membrane was 7% and 30% depending on the instruments applied (Piezosurgery and drill, respectively).…”
Section: Introductionmentioning
confidence: 99%
“…También se han analizado diferentes métodos para abrir la ventana ósea sin lacerar la membrana sinusal en la técnica de abordaje lateral. Para ello, se han descrito varias opciones como el uso de material rotato-rio, trefinas, ultrasonidos y el láser (17). Según un estudio de Peñarrocha-Diago y cols.…”
Section: Técnicasunclassified
“…Aunque la elevación del suelo del seno maxilar con fines implantológicos es uno de los procedimientos más predecibles de aumento óseo, muestra un mayor porcentaje de fracasos comparada con implantes colocados en hueso nativo (39,40). Estos resultados pueden deberse a complicaciones intraoperatorias (perforación de la membrana sinusal, fractura del reborde alveolar residual, obstrucción del ostium sinusal, hemorragia y lesión de los dientes adyacentes), complicaciones postoperatorias tempranas (hemorragia, dehiscencia de la herida, infección aguda, exposición de la membrana, infección o pérdida del injerto y fracaso del implante) y postoperatorias tardías (pérdida del injerto o del implante, migración del implante, fístula bucosinusal, dolor y sinusitis crónicas) (17).…”
Section: Técnicasunclassified
“…The produced piece of bone can be used as a barrier membrane or crushed to be used as particulate graft material for sinus floor augmentation (8). The advantages of sinus augmentation using the trephine osteotomy technique are: (I) less time is needed for performing the lateral window leading to the sinus cavity, (II) trephine osteotomy is a more precise osteotomy, (III) smaller or larger osteotomy can be prepared with several available trephine sizes according to the size and anatomy of the sinus ( 7), (IV) reducing the surgical cost, as the trephine drills are used on the same handpiece for implant placement (9), and (V) the round bony segment resulting from the lateral window osteotomy will act as a barrier so, there would be no need for a barrier membrane. Thus, the surgical cost will be less (7).…”
Section: Introductionmentioning
confidence: 99%